The Health-Income Nexus for Malaysia: ARDL Cointegration and Rao’s F-test for Causality - Tang, Chor Foon (Asian Journal of Empirical Research, 2012)
This study re-visits the health-income nexus for Malaysia using alternative econometric techniques which addressed on the small sample problem. This study covers the period of 1970-2009. Based on the appealing small sample properties, we apply the bounds testing approach to cointegration and the system-wise Rao?s F-test with bootstrap simulation procedure. The bounds test suggests close relationship between health care expenditure and real income in the long-run. In addition, the long-run income elasticity is also estimated using four long-run estimators, namely OLS, DOLS, FMOLS, and ARDL. Interestingly, the estimators suggest that the long-run income elasticity is more than unity. Therefore, our findings support the health care luxury hypothesis in Malaysia. From policy view point, the system-wise Rao?s F-test reveals unilateral causality running from real income to health care expenditure in Malaysia.